2019
DOI: 10.1097/sap.0000000000001805
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthetic Blocks in Plastic Surgery Using Portable Ultrasound

Abstract: Background With the introduction of latest generation ultrasound technology and its easy availability and portability, regional anesthetic blocks, which were formally in the domain of anesthesiologists, have now become available to practicing plastic surgeons. Enhanced Recovery After Surgery protocols for other specialties such as orthopedics and colorectal surgery have incorporated regional anesthetic blocks. These regional blocks have been shown to be effective in improving the patient comfort an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This is not surprising, as the propagation of the anesthetic bolus in the TAP plane would sometimes not cover the entire abdominal wall while being visualized with ultrasound. The 4-quadrant approach (subcostal and iliohypogastric injections) ensures that the TAP plane bolus extends all the way to the costal margin above and to the iliac crest below to cover dermatomes T7–L1 16,18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not surprising, as the propagation of the anesthetic bolus in the TAP plane would sometimes not cover the entire abdominal wall while being visualized with ultrasound. The 4-quadrant approach (subcostal and iliohypogastric injections) ensures that the TAP plane bolus extends all the way to the costal margin above and to the iliac crest below to cover dermatomes T7–L1 16,18 …”
Section: Discussionmentioning
confidence: 99%
“…Our method of 4-quadrant TAP blocks was published in this Journal and includes bilateral subcostal approaches to cover dermatomes T6-T10 and bilateral iliohypogastric approaches to cover T10-L1. 16,18 For these injections, a dilute solution of liposomal bupivacaine (Exparel; Pacira Pharmaceuticals, www.pacira.com) was used (20 cc Exparel + 50 cc 0.25% bupivacaine + 30 cc intravenous normal saline + 0.5 cc 1:1000 epinephrine). Twenty milliliters was used at each of the 4 injection sites, and the remaining 20 cc was infiltrated into the lower half of the abdominoplasty incision at the end of the case.…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of authors have confirmed the safety of the postoperative infusion of lidocaine in doses ranging from 3,200mg to 6,000mg over a 48 hour period. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the past few years, the use of interfacial plane blocks has been more and more advocated, 20 including erector spinae plane blocks (ESPB) for thoracic surgery, [21][22][23][24][25] pectoralis and serratus blocks for breast surgery [26][27][28][29] and quadratus lumborum (QL) blocks for abdominal surgery, 30 Intravenous lidocaine (IV lido) infusions have been demonstrated to be an effective technique for postoperative analgesia in several different types of surgery, including abdominal, [31][32][33][34] thoracic, 35,36 and spine. 37,38 We hypothesized that SNBs followed by IV lido would be as effective as CNBs.…”
Section: Introductionmentioning
confidence: 99%